Peranan Full Gospel Business Men's Fellowship International (FGBMFI) dalam Menjangkau Jiwa di Marketplace: Sebuah Kajian Reflektif Yohanes 15:16 - Marco Tanumihardja; Paulus Kunto Baskoro (Sekolah Tinggi Teologi Borneo, 2022)
Abstract: The great commission ia an important task in the life of a believers. The great commissionos God’s desire. God longs for every tribe, people, nation, and language to know and accept the LordJesus as the only Savior, according to Matthew 28:19-20. The essence of the great commission is sothat everyone can know and accept the Lord Jesus as the only personal savior for each person, andobtain eternal life. Seeing this great importance, the authors see that the outreach to the soul amongthe Full Business Men’s Fellowship International (FGBMFI) businessmen, even though they havebroad marketplace potential. The method used is descriptive literature method. This research willdiscuss effective methods of evangelism, so that evangelism is more effective and can applied in allages. The purpose of this writing is First, how important it is to outreach souls for those who don’tbelieve in Jesus. Second, the function of the Full Gospel Business Men’s Fellowship InternationalTeam, especially in West Java 2, can be maximized and many people are saved. Third, setting anexample in the management of the West Java FGBMFI regarding outtearch.Keywords: full gospel, soul, marketplace, John 15Abstrak: Amanat agung merupakan tugas yang penting dalam kehidupan orang percaya. Amanatagung adalah kerinduan Tuhan. Tuhan rindu agar setiap suku, kaum, bangsa dan bahasa dapatmengenal dan menerima Tuhan Yesus sebagai satu-satunya Juruselamat, menurut Matius 28:19-20.Inti amanat agung adalah agar setiap orang dapat mengenal dan menerima Tuhan Yesus sebagaisatu-satunya juru selamat pribadinya masing-masing, dan memperoleh hidup kekal. Melihatpentingnya agung ini, penulis melihat belum maksimalnya penjangkauan jiwa dikalangan bisnismanFull Gospel Business Men's Fellowship International (FGBMFI), padahal mereka memiliki potensimarketplace yang luas. Metode yang digunakan adalah metode deskriptif literatur. Penelitian iniakan membahas tentang cara yang efektif dalam penginjilan, sehingga penginjilan lebih tepat gunadan dapat diaplikasikan dalam segala zaman. Tujuan dalam penulisan ini adalah Pertama, betapapentingnya penjangkauan jiwa bagi yang belum percaya Yesus. Kedua, fungsi Tim Full GospelBusiness Men’s Fellowship International, khususnya bisa maksimal dan banyak orang diselamatkan.Ketiga, memberikan keteladanan dalam kepengurusan FGBMFI Jabar tentang penjangkauan jiwa.Kata kunci: full gospel, jiwa, marketplace, Yohanes 15